Correlation of Infinium HumanMethylation450K and MethylationEPIC BeadChip arrays in cartilage - Kathleen Cheung; Marjolein J. Burgers; David A. Young; Simon Cockell; Louise N. Reynard (Epigenetics, 2020)
DNA methylation of CpG sites is commonly measured using Illumina Infinium BeadChip platforms. The Infinium MethylationEPIC array has replaced the Infinium Methylation450K array. The two arrays use the same technology, with the EPIC array assaying almost double the number of sites than the 450K array. In this study, we compare DNA methylation values of shared CpGs of the same human cartilage samples assayed using both platforms. DNA methylation was measured in 21 human cartilage samples using the both 450K and EPIC arrays. Additional matched 450K and EPIC data in whole tumour and whole blood were downloaded from GEO GSE92580 and GSE86833, respectively. Data were processed using the Bioconductor package Minfi. DNA methylation of six CpG sites was validated for the same 21 cartilage samples by pyrosequencing. In cartilage samples, overall sample correlations of methylation values between arrays were high (Pearson’s r > 0.96). However, 50.5% of CpG sites showed poor correlation (r < 0.2) between arrays. Sites with limited variance and with either very high or very low methylation levels in cartilage exhibited lower correlation values, corroborating prior studies in whole blood. Bisulphite pyrosequencing did not highlight one array as generating more accurate methylation values. For a specific CpG site, the array methylation correlation coefficient differed between cartilage, tumour, and whole blood, reflecting the difference in methylation variance between cell types. Researchers should be cautious when analysing methylation of CpG sites that show low methylation variance within the cell type of interest, regardless of the method used to assay methylation.